Layered habitats: An evolutionary model for present-day recreational needs - Stoltz, Jonathan (Frontiers in Psychology, 2022)
Urbanisation and lifestyle-related illnesses increase globally. This highlights the need to shape modern human habitats to support basic recreational needs, promoting such things as physical activity and restoration of high stress levels and cognitive fatigue. Previous research suggests eight perceived qualities in the outdoor environment, described as eight perceived sensory dimensions, as universally meaningful to people in this regard. However quite extensively studied in relation to various health and wellbeing outcomes, human sensitivity and appreciation for these qualities has not yet been explicitly analysed from an evolutionary perspective. This paper investigates their possible evolutionary roots and suggests an order for their development. This is linked with empirical findings on their relative capacity to support restoration of stress and cognitive fatigue. Qualities of earlier origin are suggested to correspond to older, more fundamental adaptations. Each subsequently developed quality implies an increased complexity of our environmental relations, associated with higher demands on more recently developed capacities. The proposed model thus links the more restorative Serene, Sheltered, Natural, and Cohesive perceived sensory dimensions with earlier stages of our development while the more demanding Diverse, Open, Cultural, and Social qualities are associated with more recent transitions. It might be of relevance when shaping modern human habitats from a health-promoting perspective, and have applications in the planning and design of, e.g., health care settings, rehabilitation gardens, urban green areas, recreational forests or other similar outdoor environments.